Preventive hyperbaric oxygen therapy improves acute graft-versus-host disease by activating the Nrf2/HO-1 pathway - Xue, Chao; Chen, Hao; Zhao, Yiou; Yuan, Dai; Fang, Xiaosheng; Ding, Mei; Qu, Huiting; Wang, Xin; Ge, Xueling; Lu, Kang; Jiang, Yujie (Frontiers in Immunology, 2025)
BackgroundHyperbaric oxygen therapy (HBOT) has been confirmed as an effective and economical therapeutic modality for treating hemorrhagic cystitis (HC), whether induced by infection or acute graft-versus-host disease (aGVHD), in transplant recipients. However, its potential benefits in treating aGVHD remain largely unknown. This study explored the effects of HBOT on aGVHD and its underlying mechanisms.MethodsThe beneficial effects of HBOT on aGVHD were investigated in a murine model. Manifestations, pathological alterations, reactive oxygen species (ROS) levels in target organs, and survival data of the recipient mice were collected. Nuclear factor erythroid-derived 2-related factor 2 (Nrf2) and its downstream enzyme heme-oxygenase 1 (HO-1) expression in mouse samples were assessed via Western blot and immunohistochemistry analyses. ML385, an Nrf2 inhibitor, was used to validate the protective role of Nrf2 in the beneficial effect of HBOT on aGVHD. Furthermore, we initiated a clinical cohort study and collected data from the patients with definite aGVHD before and after HBOT to validate the preclinical conclusions.ResultsWe found that HBOT alleviated aGVHD in mice, which was associated with a significantly prolonged overall survival (OS) and reduced pathological injury, whereas Nrf2 inhibition had the opposite effect. HBOT decreased ROS levels and proinflammatory cytokines, including IL-6 and TNF-α, while upregulated Nrf2 and its downstream antioxidant enzyme HO-1. In the clinical cohort study, the incidence of grades 1–3 aGVHD was significantly lower in the combination arm containing HBOT than in the HBOT-free cohort.ConclusionPreventive HBOT can mitigate aGVHD by activating the Nrf2/HO-1 signal transduction pathway, suggesting that HBOT may be a feasible approach for both the prevention and treatment of aGVHD.Clinical trial registrationClinicalTrials.gov, identifier NCT04502628.